Job Training, English Language Skills, and Employability: Evidence from an Experiment in Urban India - Prashant Loyalka; Dinsha Mistree; Robert W. Fairlie; Saurabh Khanna (Institute of Labor Economics (IZA), 2024)
Low-income individuals in developing countries are often inadequately prepared for employment because they lack key labor market skills. We explore how employability and wage outcomes are related to English language skills in a novel, large-scale randomized field experiment conducted in Delhi, India involving 1,260 low-income individuals. Experimental estimates indicate that a job training program that emphasizes English language skills training substantially increases English language skills as well as employability and estimated wages (as assessed by hiring managers through interviews) for regular jobs and employability for jobs that specifically require English language skills. Program effects hold regardless of gender, social class, or prior employment. We furthermore find that participants enjoy improved employability and estimated wage outcomes because the program improves their English language skills. Taken together, our results suggest that English language skills training, which is surprisingly underutilized in developing countries, may provide considerable economic opportunities for individuals from low-income backgrounds.
Keywords: C93; I25; I26; J24; O15; 330; poverty reduction; opportunities; employability; English; field experiment